2019
DOI: 10.1111/mbe.12218
|View full text |Cite
|
Sign up to set email alerts
|

See, Touch, and Feel: Enhancing Young Children's Empathy Learning Through a Tablet Game

Abstract: Ongoing research is providing new insights into the biological rudiments of empathy and its neurobiological underpinnings. There is also growing awareness that tablet technology, when used educationally and ethically, can aid adolescents and young‐adults' empathic learning. However, there has been little attempt globally to translate this new knowledge into the learning and teaching of empathy in early years education. This small‐scale study aimed at enhancing 3–6‐year‐olds' empathy by designing a tablet game … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 55 publications
(83 reference statements)
2
15
0
Order By: Relevance
“…In line with our hypothesis, the Zirkus Empathico group, compared to controls, showed improvements in our primary outcome measure empathy, reflected by greater increases in the EMK 3-6 empathy parent rating. This finding resonates with previous research reporting improvements in empathy after preschoolers engaged with a digital SEC training in the classroom setting (Wu & Kim, 2019). Interestingly, no training group differences were detected for the GEM empathy parent rating as further primary outcome.…”
Section: Sec Measure Associations With P3 Amplitudessupporting
confidence: 90%
See 2 more Smart Citations
“…In line with our hypothesis, the Zirkus Empathico group, compared to controls, showed improvements in our primary outcome measure empathy, reflected by greater increases in the EMK 3-6 empathy parent rating. This finding resonates with previous research reporting improvements in empathy after preschoolers engaged with a digital SEC training in the classroom setting (Wu & Kim, 2019). Interestingly, no training group differences were detected for the GEM empathy parent rating as further primary outcome.…”
Section: Sec Measure Associations With P3 Amplitudessupporting
confidence: 90%
“…Sample size was estimated with G*Power (Faul et al, 2007), assuming a 20% attrition rate (e.g., Wadepohl et al, 2011) and a medium effect for the primary measure of empathy regarding group differences after a digital SEC training (e.g., Wu & Kim, 2019).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empathic concern, in turn, serves as the antecedent of valuing others’ wellbeing (Batson, Eklund, Chermok, Hoyt, & Ortiz, ) and is a driver for prosocial behaviour (FeldmanHall, Dalgleish, Evans, & Mobbs, ). The positive relation between playing the Empathy World and enhanced empathic perception is supported by a brain imaging study showing enhanced empathic sensitivity to harming social interactions and increased attention to others' feelings from teachers’ observations (Wu & Kim, ). These results suggest that hybridity design focusing on digitalising empathic perception can modulate the way these children “see” social situations through developed selective attention and a longitudinal selective tendency .…”
Section: Discussionmentioning
confidence: 90%
“…Another limitation of this study is a lack of evidene showing how hybrid design mediated social learning would necessarily translate into real‐life social situations. While a recent study has shown that playing the Empathy World has increased children’s attention to other’s feelings in teachers’ observations (Wu & Kim, ), how hybridised game design and engagement in gameplay can promote real‐life prosocial behaviour and emotion understanding calls for further study.…”
Section: Discussionmentioning
confidence: 99%